Les cobertes del missal de Sant Ruf de la catedral de Tortosa, una obra d'orfebreria singular de finals del segle XII - Sanjosé i Llongueras, Lourdes de (Miscel·lània litúrgica catalana, 2019)
In this paper we discuss the covers of the St Rufus Missal of Tortosa Cathedral (ms. 11) in order to determine their filiation and dating. To thisend, we analyse the most significant features of the two representations, the Maiestas Domini and the Crucifixion, comparing them with metal works (book covers and others) from Limoges, the Meuse region, the Silos workshop and the Catalan workshops. We analyse the coincidences and discrepancies in relation to the works of these workshops. The conclusion is reached that it is an unicum, the work of an artist who was directly or indirectly familiar with those workshops and produced a completely personal creation. Our hypothesis is that he was a foreign master who was working in Catalonia at the end of the 12th century.